2019
DOI: 10.1055/s-0039-3401369
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Minimum Antibacterial Values of Different Medicaments Used in Endodontic Regenerative Procedures

Abstract: Objectives This study aimed to evaluate the cytotoxicity of minimum antibacterial values of medicaments used in endodontic regeneration on stem cells. Materials and Methods “Minimum inhibitory concentration,” “minimum bactericidal concentration,” and “minimum biofilm inhibitory concentration” of triple and double antibiotic paste, a modified triple antibiotic paste (minocycline replaced by clindamycin), Augmentin, and calcium hydroxide were determined using Enterococcus faecalis (ATCC 29212) by microtiter plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…In our study, calcium hydroxide exposure up to 25 µg/mL did not significantly affect the viability of dental pulp stem cells after 48 h. In contrast, a previous study showed that calcium hydroxide is not toxic for stem cells of the apical papilla (SCAPs) and increases cell survival and proliferation [23]. However, an evaluation of calcium hydroxide's cytotoxicity towards SCAPs at its minimum bactericidal concentration showed higher toxicity than antimicrobial combinations [24]. Our study presents a similar result, additionally highlighting that both concentration and time of exposure contribute to its cytotoxic effect.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study, calcium hydroxide exposure up to 25 µg/mL did not significantly affect the viability of dental pulp stem cells after 48 h. In contrast, a previous study showed that calcium hydroxide is not toxic for stem cells of the apical papilla (SCAPs) and increases cell survival and proliferation [23]. However, an evaluation of calcium hydroxide's cytotoxicity towards SCAPs at its minimum bactericidal concentration showed higher toxicity than antimicrobial combinations [24]. Our study presents a similar result, additionally highlighting that both concentration and time of exposure contribute to its cytotoxic effect.…”
Section: Discussioncontrasting
confidence: 77%
“…20 The results show that TAP has antibacterial effectiveness against E. faecalis. These results align with the research of Khoshkhounejad et al 21 stated that TAP with clindamycin modification can inhibit and kill E. faecalis.A study conducted by Sabrah et al 22 showed that at a concentration of 300 µg/mL, the TAP consisting of metronidazole, ciprofloxacin, and minocycline showed bactericidal activity against E. faecalis.…”
Section: Discussionsupporting
confidence: 91%
“…Vice versa, high concentrations of TAP or DAP (1000 mg/mL) altered SCAPs viability [72]. According to a recent study, TAP induced less cytotoxic effect against SCAPs and it is the safest antibiotic, compared to DAP and Ca(OH) 2 [89]. Alghilan et al indicated that TAP enhanced the attachment of DPSCs to the dentin, while, TAP, DAP, and Ca(OH) 2 reduced DPSCs proliferation [76].…”
Section: Comparison Among Medicamentsmentioning
confidence: 99%